A human rights mechanism for ASEAN - Padilla, David J. (2007)
Regional intergovernmental human rights mechanisms have been established by regional international organizations in most of the world. The council of Europe, by treaty, created the European Court of Human Rights. The Organization of American States established, by treaty, the Inter-American Commission on Human Rights and the Inter-American Court of Human Rights. The African Union has also established an African Commission on Human and People's Rights as well as the African Court of Human and Peoples' Rights. Asia has no overarching regional international organization. However, ASEAN recently adopted a Charter that is now being ratified by the ten founding member states. The Charter contemplates the creation of an eventual regional human rights mechanism for human rights. This prospect is the culmination of the efforts of ASEAN's working group on human rights, composed of government representatives, non-governmental human rights organizations and academicians.
Keywords: Human rights; Civil rights